PERANCANGAN HOTSPOT MENGGUNAKAN MIKROTIK PADA KANTOR PELAYANAN KEKAYAAN NEGARA DAN LELANG (KPKNL) PURWOKERTO - Hellyana, Corie Mei (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Bina Sarana Informatika, 2021)
The provision of hotspot services is currently very necessary, not only students, teachers, lecturers, employees but also the general public also need hotspot service when they are in a place. KPKNL Purwokerto, as a state asset and auction service agency, also provides hotspots for employees to support work activities. However, at KPKNL Purwokerto, for the security side of the network using WPA2-PSK, many unauthorized parties can still penetrate because the password has been leaked. Then, the absence of a bandwidth limitation for each user is one of the causes of uncontrolled internet use. From some of these problems, it is proposed to add an access point for hotspot facilities for guests for their convenience, move the access point to a place where the signal can be reached properly by all client PCs and optimize the mikrotik routerboard that has been used in the network to solve network security problems. and bandwidth. Mikrotik is used to create a captive portal / login page using the hotspot server feature as well as for bandwidth management. The result of the configuration on this proxy is that each employee and guest must enter the username and password that has been registered on the proxy to be able to access the internet with limited bandwidth according to the user profile.